A review of Cyaforma Wang (Diptera: Tephritidae), with some biological notes on the genus - Chen, Xiaolin; Wang, Yong; Huangfu, Ning (Zootaxa, 2024)
Species of the genus Cyaforma Wang are reviewed. One new species, C. chayuica Chen from Xizang, China is described and illustrated. C. tonkinensis (Zia) is newly recorded from China. The males of C. macula (Wang) and C. tonkinensis are described for the first time. A key to the known species of this genus is provided. Additionally, biological notes on the genus are reported.